Hybrid Fuzzy PID Controller for Pressure Process Control Application - Anitha, T. (Institute of Electrical and Electronics Engineers Inc., 2019)
Process of controlling pressure in process industries becomes difficult when the conventional controller is used because of not capable of handling delay time, rise time and steady-state error. So, in this work, the method of the combining the conventional controller with the optimised hybrid system is considered. In this hybrid system the combination of fuzzy logic controller and PID controller is taken for evaluation and performance analysis over the pressure process. Generally fuzzy controllers use a rule base to describe relationships between the variables that are used in the processes. The performance analysis is done for different conventional controllers like PID and fuzzy PID. The performance analysis for the controllers is based in considering conventional resultant parameters like rise time, peak overshoot and settling time. We proposed a hybrid fuzzy PID controller which utilises the properties and advantage of the fuzzy and PID controllers. The effectiveness of the Hybrid fuzzy PID controller designed is demonstrated in pressure process. Â© 2019 IEEE.